Exploration of Vision and Language in Education: A Bibliometric Study and Its Implications - I. S. Mannesa, Muh. Nur Haq; Sabriasrifah, Sabriasrifah; Pujhana, I Kadek Wahyu; Koesrohmaniah, Sri; Sulastri, Augustina (PROMOTOR, 2025)
This research aims to identify the specific contributions of vision and language technology to educational outcomes and to explore how these technologies can be used in current teaching practices. Using bibliometric analysis, clustering, and publications in the field of neuropsychology, this research examines the theoretical relationship between "Vision" and "Language" in the context of education. This research uses a quantitative method with a bibliometric approach to map and analyze 4,542 documents, consisting of 3,125 documents from Scopus publications and 1,414 documents from Web of Science publications from the period 1987 to 2025. This research reveals the most influential authors, collaboration maps, institutions, the most productive countries, research trends, developments, papers, and key concepts in the field of vision and language research in the context of education. The findings and conclusions of the study show the factors influencing public perception of educational research and the importance of literature in developing educational ideas and integrating productivity and environment for significant contributions in the areas of "Vision" and "Language." This study also emphasizes the importance of using literature in a variety of fields, including theoretical studies and practical applications.